RESEARCH OF THE VALUE AND SENSE PICTURE OF THE WORLD JUNIOR SCHOOLCHILDREN IN THE COURSE OF THEIR EDUCATIONAL ACTIVITIES (Pedagogy of Higher and Secondary Education, 2022)
In the articles demonstrated the relevance of the problem of education praice formation children. Article demonstrated diagnostic meted praise formation children in the reality and future.
Keywords: praise formation picture children; praise formation picture childrenvalue; orientation; subject perceive education problem